Screening of Anti-Diabetic Activity of Physalis Minima Fruits - K. Sunitha; A. Srinivas Nayak (International Journal of Pharma and Bio Sciences, 2020)
The plants are a vast resource of phytoconstituents which could treat different diseases. The methanolic extract of Physalis minima fruits was screened for anti-diabetic activity. The literature survey revealed that these studies were not reported earlier. So, the present research study was aimed to reveal the anti-diabetic activity of Physalis minima fruits. The results concluded that the extract possess anti-diabetic activity. The study showed good significance in repair of damaged β-cells in diabetic Physalis minima fed rats, when compared to diabetic control animals. Ithas been concluded that Physalis minima extract showed hypoglycaemic activity on prolonged treatment and is also regenerating β- cells and so it could be used in the treatment of diabetes mellitus.